BLOOD PRESSURE FLUCTUATIONS IN CYCLIC DIALYSIS IN PATIENTS WITH END-STAGE CHRONIC RENAL FAILURE AT BACH MAI HOSPITAL IN 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe blood pressure fluctuations in patients with end-stage renal disease on dialysisat Bach Mai Hospital and related factors.Study subjects and methods: Cross-sectional description was performed on 256 chronic renalfailure patients undergoing cyclic hemodialysis.Results: The rate of blood pressure fluctuations during and after hemodialysis was 74.6%, includingfluctuations in blood pressure and hypotension. The factors of age, associated hypertension, economiccircumstances, health insurance regime, time of hemodialysis, and self-care ability are statisticallysignificant with the patient’s BPH with p < 0,05.Conclusion: Blood pressure fluctuations often occur at any time during and after dialysis, mostnecessary to closely monitor the patient to promptly detect blood pressure complications for timelytreatment.
Keywords: Blood pressure fluctuations, hemodialysis.